1997
DOI: 10.1046/j.1469-7580.1997.19110001.x
|View full text |Cite
|
Sign up to set email alerts
|

Review. Articular cartilage chondrons: form, function and failure

Abstract: The chondrocyte and its pericellular microenvironment together represent the chondron, historically considered the primary structural, functional and metabolic unit of articular and other hyaline cartilages. This review summarises research over the last 10 years to establish the molecular anatomy, functional properties and metabolic contribution of the chondron in articular cartilage homeostasis, and its failure during the initiation and progression of degenerative osteoarthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
318
0
22

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 380 publications
(346 citation statements)
references
References 27 publications
6
318
0
22
Order By: Relevance
“…That chondrocytes of the middle and deep zones can be grouped in single, double or multiple chondron columns with interconnecting segments between adjacent chondrons has been reported for non-degenerative tibial cartilage (Poole, 1997). It has been suggested that chondrocyte groups may have formed during skeletal development (Morrison et al, 2000), and their pairing may have arisen after cell division followed by an incomplete separation within the chondron microenvironment (Chi et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That chondrocytes of the middle and deep zones can be grouped in single, double or multiple chondron columns with interconnecting segments between adjacent chondrons has been reported for non-degenerative tibial cartilage (Poole, 1997). It has been suggested that chondrocyte groups may have formed during skeletal development (Morrison et al, 2000), and their pairing may have arisen after cell division followed by an incomplete separation within the chondron microenvironment (Chi et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Its histomorphology is dominated by an extracellular matrix (ECM) consisting mainly of proteoglycan and type II collagen. Although cells of articular cartilage are represented by relatively sparsely distributed chondrocytes (Kuettner et al, 1991;Stockwell, 1971), articular chondrocytes and their pericellular microenvironment, termed chondrons, function as the primary metabolic units of articular cartilage to maintain matrix homeostasis via a synchronized balance between anabolism and catabolism (Kuettner et al, 1991;Poole, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The pericellular matrix is a thin zone, different in composition to the interterritorial matrix, which surrounds each cell [4] and is believed to be an important element in this comunication.…”
Section: Introductionmentioning
confidence: 99%
“…In normal cartilage, the PCM is often defined by the exclusive presence and localization of type VI collagen around the chondrocytes [8 -11] and is characterized by an elevated concentration of proteoglycans and glycoproteins relative to the surrounding ECM [12][13][14]. While the exact function of the PCM in cartilage is not fully understood, it is thought to play an important biomechanical role in the tissue.…”
Section: Introductionmentioning
confidence: 99%